Productivity and calibre distribution of three green asparagus hybrids in the province of San Luis, Argentina, in their sixth production year (2015) - Bazán, P. (2018)
Fil: Bazán, P. Universidad Nacional de San Luis. Facultad de Ingeniería y Ciencias Agropecuarias; Argentina